2023
DOI: 10.21037/hbsn-22-421
|View full text |Cite
|
Sign up to set email alerts
|

An international Delphi consensus statement on metabolic dysfunction-associated fatty liver disease and risk of chronic kidney disease

Abstract: Background: With the rising global prevalence of fatty liver disease related to metabolic dysfunction, the association of this common liver condition with chronic kidney disease (CKD) has become increasingly evident. In 2020, the more inclusive term metabolic dysfunction-associated fatty liver disease (MAFLD) was proposed to replace the term non-alcoholic fatty liver disease (NAFLD). The observed association between MAFLD and CKD and our understanding that CKD can be a consequence of underlying metabolic dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 135 publications
1
25
0
Order By: Relevance
“…Hepatocytic ballooning has been associated with greater severity of liver disease and higher risk of developing liver‐related complications, cardiovascular disease and chronic kidney disease 1,2 . Matteoni et al 3 reported that liver‐related deaths occurred more frequently in patients in whom liver biopsies showed hepatocytic ballooning, Mallory‐Denk bodies (MDBs) or fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocytic ballooning has been associated with greater severity of liver disease and higher risk of developing liver‐related complications, cardiovascular disease and chronic kidney disease 1,2 . Matteoni et al 3 reported that liver‐related deaths occurred more frequently in patients in whom liver biopsies showed hepatocytic ballooning, Mallory‐Denk bodies (MDBs) or fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…10,18 These findings are also in line with a Delphi-based consensus statement reached from a multidisciplinary panel of international experts, supporting the existence of a significant association between PNPLA3 p.I148M variant and risk of kidney dysfunction. 19 To our knowledge, there is currently little information about the association between the PNPLA3 p.I148M variant and decreasing levels of eGFR, even within the normal range, in individuals with metabolic dysfunction and without advanced kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…CKD has become a major public health issue, with a global prevalence estimated to be 8-16% [5]. To date, there is growing evidence that the increasing global prevalence of MAFLD will further increase the incidence of CKD worldwide [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%